Comparative expression analysis of HSP genes in wheat and barley under heat stress - Kaur, Amandeep; Gupta, Om Prakesh; Sharma, Pradeep (Journal of Cereal Research, 2016)
Plants are consistently exposed to numerous biotic (herbivore and pathogen) and abiotic stresses (cold, drought, salinity, heat etc.). Being sessile organism, they cannot escape therefore, during the course of evolution they have evolved with sophisticated mechanism of tolerance. Among abiotic stresses, heat stress is one of the key stresss which causes great loss to the plants (Vinocur and Altman, 2005). Heat stress has asignificant adverse impact on carbon assimilation and starch synthesis in these environments, which leads to reduction of grain yield and quality. In this heat acclimatization process, heat shock proteins (HSPs) play an important role in regulation of this heat-induced transcriptional reprogramming (Al-Whaibi, 2010). Heat shock proteins (HSPs) are evolutionary conservedproteins which are induced in almost all organisms byhigh temperature and other abiotic and biotic stresses.